Interpersonal harm aversion as a necessary foundation for morality: A developmental neuroscience perspective. (19th April 2017) - Decety, Jean; Cowell, Jason M.
Abstract: Growing evidence from developmental psychology and social neuroscience emphasizes the importance of third-party harm aversion for constructing morality. A sensitivity to interpersonal harm emerges very early in ontogeny, as reflected in both the capacity for implicit social evaluation and an aversion for antisocial agents. Yet it does not necessarily entail avoidance toward inflicting pain to others. Later, an understanding that harmful actions cause suffering emerges, followed by an integration of rules that can depend on social contexts and cultures. These developmental findings build on a burgeoning literature, which suggests that the fundamental nature of moral and social cognition, including their motivational and hedonic value, lies in general computational processes such as attention, approach–avoidance, social valuation, and decision making rather than in fully distinct, dedicated neural regions for morality. Bridging the gap between cognition and behaviors and the requisite affective, motivational, and cognitive mechanisms, a developmental neuroscience approach enriches our understanding of the emergence of morality.